Alef, mem, tau : kabbalistic musings on time, truth, and death - Wolfson, Elliot R. (University of California Press, 2006)
This highly original, provocative, and poetic work explores the nexus of time, truth, and death in the symbolic world of medieval kabbalah.
Keywords: Time -- Philosophy.; Time -- Religious aspects -- Judaism.; Cabala -- History.; Temps -- Philosophie.; Kabbale -- Histoire.; RELIGION -- Judaism -- Kabbalah & Mysticism.; RELIGION -- Judaism -- General.; Cabala; Time -- Philosophy; Time -- Religious aspects -- Judaism; Humaniora -- Religionsvidenskab.; Humaniora -- Jødisk kultur og historie.; History